Empirically Identified Subgroups of Children Served in Part C Early Intervention Programs. Issue 7 (September 2017) - Elbaum, Batya; Celimli-Aksoy, Seniz
ABSTRACT: Objective: Early intervention (EI) programs under Part C of the Individuals with Disabilities Education Act serve a developmentally heterogeneous population of infants and toddlers with or at risk of developmental delays or disabilities. The aim of this study was to identify empirically distinct subgroups of children in EI so as to inform early prognosis and service planning. Methods: We applied mixture modeling to developmental assessment data from 1513 children who enrolled in a large, urban EI program between 2009 and 2013. The observed variables were children's EI-entry developmental quotients (DQs) in 5 domains (communication, cognitive, motor, adaptive, and personal–social) as assessed by the Battelle Developmental Inventory, Second Edition. Results: A 4-class model showed the best fit to the data, revealing subgroups with distinct developmental profiles. Children in the first subgroup showed a severe delay in communication with less severe delays in the other domains. Children in the second subgroup likewise showed a severe delay in communication, but with comparably severe delays in the cognitive and motor domains. Profiles for the third and fourth subgroups showed the same overall patterns as those for the first and second subgroups, respectively, but to a less severe degree. Developmental trajectories differed by subgroup. Conclusion: Consideration of subgroups based on children's developmental assessment scores provides insight into underlying commonalities among children with different presenting diagnoses on entry into EI. The subgroups also have clinical relevance in terms of both practitioners' and parents' understanding of children's likely service needs and developmental trajectories.